Effective conductivity of isotropic composite with Kapitza thermal resistance - Kien, Nguyen Trung; Luat, Nguyen Van; Chinh, Pham Duc (Vietnam Journal of Mechanics, 2018)
A simple method is introduced for computing the effective conductivity of isotropic composite with imperfect interface. Based on the doubly-coated circle assemblage model, one can determine the effective thermal conductivity of the composite. The application of this model to the composite with imperfect interface of the Kapitza’s type is proposed. The results obtained were compared with the Fast Fourier Transform simulation and the equivalent inclusion approximation in 2D show the effectiveness of the methods.